India : Social Security for the Unorganised Sector - World Bank (Washington, DC, 2013)
The objective of this Non Lending Technical Assistance (NLTA) is to assist the Government Of India (GOI) to formulate - and where relevant initiate implementation of - financially and administratively feasible policy responses to address the large gap in social security coverage that currently prevails in India. The ultimate objective of this policy would be to gradually expand financially sustainable income protection through social insurance for lower income households in the unorganized sector for major risks including health, disability, death and old age. The NLTA was initiated in response to a request from the Ministry of Labour, GOI and formally requested through a letter from DEA in late 2006. At the IMT review of the NLTA in 2007, the CMU requested periodic updates on progress and this note is the first of those.